Halochromic sensors for real-time monitoring of spoilage of packed seer fish. (2020) - Devarayan, Kesavan; Pandiyan, Padmavathi; Nagaraju, Kopperundevi Sivakami; Anjappan, Hema
Abstract: Development of halochromic thin film sensors for monitoring the degree of spoilage of packaged seer fish is described in this study. Three halochromic thin film sensors were prepared by combining a halochromic dye with starch/potato dextrose agar, polyvinyl alcohol, and cellulose acetate and characterized using Fourier-transform infrared spectroscopy. The halochromic sensors were tested for monitoring spoilage of packaged seer fish at ambient temperature, refrigerated, and frozen conditions. The halochromic response of the thin film sensors was evaluated by image processing and color measurements such as CIE Lab and RGB value determinations. All the three thin film sensors exhibited excellent color changes in proportion with the spoilage of the packed seer fish. These halochromic thin film sensors are useful for real-time monitoring of spoilage of packed seafood.